Octa-band reconfigurable monopole antenna frequency diversity 5G wireless - Ali Kadhum Abd; Jamal Mohammed Rasool (International Journal of Electrical and Computer Engineering (IJECE), 2023)
An octa-band frequency-reconfigurable antenna (28×14×1.5 mm3) with a broad tuning range is shown. Antenna mode1 (4.31 GHz) works in one single-band mode and two dual-band in modes 2 and 3 (i.e., 3.91 and 5.9 GHz) as well as one tri-band in mode 4 (i.e., 3.09, 5.65, and 7.92 GHz) based on the switching situation of the antenna. Changing capacitance for frequency reconfigurability is accomplished with the use of lumped components. The antenna’s observed tuning spans from 3.09 GHz to 7.92 GHz. for all the resonant bands, the suggested antenna has a voltage standing waves ratio (VSWR)<1.45 except for one band with a VSWR<1.85. From 70.57% to 97.93%, the suggested structure’s radiation efficiency may be calculated. For a better understanding proposed antenna’s far field and scattering characteristics, we used CST Microwave Studio 2021. We may conclude that our suggested antenna is suitable for today’s wireless applications, which need multiband and multimode small antennas. Using a small stainless-steel wire as a switch, a prototype of the antenna design is built and tested to verify the simulation findings. The suggested reconfigurable antenna’s strong concordance between simulated and measured findings.